Peningkatan Aktivitas Pembelajaran Penjumlahan Pecahan dengan Strategi Pembelajaran Inkuiri di Kelas IV SDN 10 Sungai Limau Kabupaten Padang Pariaman - Analia, Riri; Masniladevi, Masniladevi; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by the experience experienced by researchers in elementary schools about the implementation of fraction addition learning in class IV SDN 10 Sungai Limau, Padang Pariaman Regency, where the learning outcomes obtained by students are generally under the Minimum Mastery Criteria (KKM), which is 70. This is because the number of students who are not active in the learning process. To overcome these problems, inquiry learning strategies are used. The purpose of this study is to describe the plan of implementing learning, implementing learning and increasing fraction addition learning activities with inquiry strategies. This research includes: 1) planning, 2) implementation, 3) observation, and 4) reflection. Research data in the form of learning plan data, teacher activity data student activity data, learning activity data and learning achievement tests. The research subjects consisted of teachers and class IV students at totaling 15 students. The results of the study on the assessment of the RPP for the first cycle scored 79% while in the second cycle the assessment of the RPP got a score of 96%. The implementation phase of the teacher aspect in the first cycle scored 79%, increasing in the second cycle to 96%. The implementation phase of the aspects of students in the first cycle scored 66%, increasing in the second cycle to 92%. Student learning outcomes in cycle I got a score of 73, increased in cycle II to 87. It can be concluded that the inquiry strategy can increase fraction learning activities in class IV.